تدريب اللغة العربية لفهم معاني القراءات في الصلاة تحقيقا للخشوع في الصلاة لأهل المجمع السكني مانغالا بماكسر: Arabic Language Training to Understand Prayer Recitations: Enhancing Worship Quality For the Residents of Gubernuran Manggala Makassar - Mahmuddin, Ronny (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to teach Arabic to help the residents of Gubernuran Manggala Makassar understand the meanings of prayer recitations. The problem addressed is the residents' current level of understanding regarding prayer recitations and its solution through Arabic language training. This qualitative research uses interviews and participatory observation, beginning with an observation of the residents' conditions and an analysis using the SOAR framework, which led to the development of a work plan and activities. The training was conducted over two months, including a pre-test, the training itself, and a post-test. Before the training, most participants were unaware of the meanings of prayer recitations, while a small number had limited understanding. After the training, participants were able to understand the meanings of the prayer recitations. Post-test results showed that participants achieved satisfactory scores, ranging from 60 to 100. The participants also felt a significant improvement in their prayers. The study recommends that such training programs be continued in other locations, especially around Manggala, in collaboration with religious institutions and with government support.